Features of communication of a doctor with special groups of patients and in conflict situations. - Usenko, L. V.; Krishtafor, A. A.; Tiutiunnyk, A. H.; Petrashenok, Ye V.; Oleniuk, D. V.; Machuzhak, H. A.; Skulinets, O. B. (Medicni Perspektivi, 2019)
The article describes an important component of the medical process which should be paid a special attention: the preparation of a young doctor – the communication between the physician and the patient and his relatives. Distinctive features of a modern patient: the tendency to control the state of his own health with simultaneous irresponsible attitude towards it; when revealing a disease, he/she is looking for the worst in himself/herself; the reduction of the moral character against the background of a decline in the morals of society, which affects the culture of the patient's behavior, makes him/her more aggressive; a modern patient is more lenient to himself/herself with an extremely demanding attitude to the doctor. Several interrelated functions of communication are distinguished: informational, interactive, perceptual, emotive (affective-commutative). The levels of communication are distinguished: social-role (ritual); business; intimate-personal. There are three types of communication: imperative; manipulative; dialogical (based on equal partnership). In the process of communication of the physician with patients, depending on the circumstances, two systems of communication can be used: verbal and nonverbal. In the relationship "patient-physician" R. Witch identifies 4 models: paternalistic, technocratic, collegian, and contractual. Each patient needs an individual approach, individual forms of communication and measures of physician’s psychotherapeutic influence, especially in the communication of the doctor with so-called “difficult” patients, as well as at the risk of conflict situations. Causes of conflict situations are: insufficient attention to the patient; characteriological features of a doctor and a patient; unreliable information about the state of health of the patient from the part of junior and middle medical personnel; lack of patient’s information consent for treatment; lack of coordination of the actions of different medical specialists; defects in the maintenance of medical records; professional incompetence.